Relatório de Estágio Curricular no Juízo Central Criminal de Lisboa - Fernandes, Catarina Isabel Teodoro (2022)
This text summarizes a curricular internship held at the Judicial Court of the District of Lisbon, specifically in the Central Criminal Court of Lisbon. Throughout the internship, I followed closely the work of a collective court, accompanying it as much as possible. I thus describe throughout this document what I have observed: hearings, deliberations, among other things. In the context of one of the cases followed, a number of questions concerning the application of coercive measures have arisen, in particular Pre-trial Detention and the impediments of a judge arising from its application during the trial. Of a practical and expository nature, Chapters I and II correspond to the probationary report itself, the remaining chapters being reserved for the discussion of the problem of the application of pre-trial detention.